The Association between Protein C and Antithrombin III Levels with the Severity of Coronavirus Disease-2019 Symptoms - Siregar, Jelita; Ihsan, Riyadh (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Coronavirus disease-2019 (COVID-19) has various symptoms ranging from mild to critical. Hypercoagulation state is often observed in severe and critical COVID-19. Both coagulation and inflammation are interrelated and amplifying each other, with protein C and antithrombin (AT) III as two important mediators. OBJECTIVE: To determine the association between protein C and AT III levels with the severity of COVID-19 symptoms. METHODS: This analytical study was conducted at Haji Adam Malik Hospital from April to July 2021. Subjects were obtained by consecutive sampling method. Inclusion criteria were patients with confirmed COVID-19 using RT-PCR and willing to participate. Subjects were divided into 2 groups: mild-moderate and severe-critical symptom groups. Demographic and blood sample were obtained from each subject. Blood samples underwent examination for leukocyte, thrombocyte, PT, aPTT, protein C, and AT III. RESULTS: A total of 50 patients were obtained with female domination (58%) and mean age of 41.44 (SD 20.90) years. Most subjects (86%) were in mild-moderate symptom group. There were significant differences in the level of protein C and AT III in both group (p= 0.029 and 0.034, respectively). Using the cut-off values for protein C of 5.36 ng/mL and AT III of 45.6%, subjects who had mediators level below the value tend to develop severe and critical symptoms compared to their counterparts (OR= 5.769 and 6.458, respectively). CONCLUSION: Protein C and AT III are associated with severity of COVID-19 symptoms. Lower protein C and AT III levels increase the risk for developing severe and critical symptoms.